Dis-Honoring the Dead: Negotiating Decorum in the Shadow of Sandy Hook. Issue 1 (1st January 2016) - Duerringer, Christopher M.
Abstract : Mourning the indiscriminate murders of 26 children and adults at Sandy Hook Elementary School, many eulogizers began calling publicly for gun control reforms that would help prevent similar tragedies in the future. One particularly savage set of responses to these efforts accused eulogizers of a gross breach of decorum that dishonored the dead and ought, therefore, to be dismissed. Drawing from a Burkean perspective that recognizes the relationships among rhetoric, decorum, and ideology, I contend that these attacks are based upon and advocate for a particular sense of decorum (one at odds with the one embodied in the rhetorical tradition) that reduces the circumference of human tragedy to the individual and permits only conformity with the status quo.